2018
DOI: 10.3233/jad-170971
|View full text |Cite
|
Sign up to set email alerts
|

Higher Blood Vitamin C Levels are Associated with Reduction of Apolipoprotein E E4-related Risks of Cognitive Decline in Women: The Nakajima Study

Abstract: Our results demonstrate significant beneficial effects of vitamins C and E in reducing the risk of cognitive decline in women with APOE E4 and men without APOE E4, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…As demonstrated in a previous study with an Alzheimer’s disease model [20], ascorbic acid co-treatment ameliorates D-gal-induced memory impairment. Noguchi-Shinohara et al (2018) recently found that a high blood level of ascorbic acid is associated with the amelioration of apolipoprotein E E4-related cognitive decline in elderly women [52]. Because ascorbic acid has a low toxicity and is a low-cost compound, it could be one of the representative antioxidants that are effective in delaying the onset and progression of Alzheimer’s disease in humans [53].…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated in a previous study with an Alzheimer’s disease model [20], ascorbic acid co-treatment ameliorates D-gal-induced memory impairment. Noguchi-Shinohara et al (2018) recently found that a high blood level of ascorbic acid is associated with the amelioration of apolipoprotein E E4-related cognitive decline in elderly women [52]. Because ascorbic acid has a low toxicity and is a low-cost compound, it could be one of the representative antioxidants that are effective in delaying the onset and progression of Alzheimer’s disease in humans [53].…”
Section: Discussionmentioning
confidence: 99%
“…Alzheimer's disease, which accounts for over half of all dementia, occurs at a greater frequency in women versus men. A study shows the higher vitamin C level reduce the risk of cognitive decline in women with APOE4 and men without APOE4 (Noguchi-Shinohara et al, 2018). Factors related to the female endocrine system are assumed to be associated with the differences observed according to the sex.…”
Section: Discussionmentioning
confidence: 99%
“…As a part of the Nakajima study, this study involved individuals aged 65 years or older with normal cognitive function during the 2006–2008 baseline survey. The study design has been described in detail previously [ 8 , 24 26 ]. We assessed participants’ cognitive status using the Mini-Mental State Examination (MMSE) [ 27 ] and Clinical Dementia Rating [ 28 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…APOE4 risk of cognitive decline may be modified by interaction with other factors; however, the role of risk modifiers or interacting factors is not well understood. In our previous longitudinal study, we found that high serum vitamin C (VC) levels during normal cognition reduce APOE4-associated risk of cognitive decline, especially in women [ 8 ].…”
Section: Introductionmentioning
confidence: 99%